Yoga lifestyle intervention reduces blood pressure in HIV-infected adults with cardiovascular disease risk factors - Cade, Todd (2010)
People living with human immunodeficiency virus infection (HIV) are at increased risk for developing cardiovascular disease (CVD). Safe and effective interventions for lowering CVD risk in HIV are high priorities. OBJECTIVE: We conducted a prospective, randomized, controlled study to evaluate whether a yoga lifestyle intervention improves CVD risk factors, virologic or immunologic status, or quality of life in HIV-infected adults more than in a matched control group. METHODS: Sixty HIV-infected adults with mild-moderate CVD risk were assigned to 20 wks of supervised yoga practice or standard of care treatment. Baseline and week 20 measures were; 2hr-oral glucose tolerance test with insulin monitoring, body composition, fasting serum lipid/lipoprotein profile, resting blood pressures, CD4+ T-cell number and plasma HIV RNA, and the Medical Outcomes Study SF-36 health-related quality of life inventory. RESULTS: Resting systolic and diastolic blood pressures were reduced more (p=0.04) in the yoga group (−5±2 and −3±1 mmHg) than in the standard of care group (+1±2 and +2±2 mmHg), despite no greater reduction in body weight, fat mass, proatherogenic lipids, or improvements in glucose tolerance or overall quality of life after yoga. Immune and virologic status was not adversely affected. CONCLUSION: Among traditional lifestyle modifications, yoga is a low cost, simple to administer, non-pharmacological, popular behavioral intervention that can lower blood pressure in pre-hypertensive HIV-infected adults with mild-moderate CVD risk factors.